Examining local sports broadcasters' use of Twitter to cross-promote on-air and online content. Issue 4 (1st October 2016) - Hull, Kevin
ABSTRACT: Local television stations in the United States are showing a decline in revenue from previous years and are searching for new ways to promote their product in an effort to increase their audience. While previous research has examined traditional promotional methods through commercials, this study addresses how television station employees are using Twitter to promote content on traditional media outlets. An analysis of 19, 649 tweets from 201 local television sports broadcasters throughout the United States found that less than 9% of their Twitter use was devoted to promoting either their television sportscast or the website. A survey of those same sportscasters revealed that station management does not encourage them to use Twitter to promote content, even during periods when ratings are collected.